Implementing multi prime RSA digital signature in Shamir’s three pass protocol / Muhammad Arif Musa Abdullah, Muhammad Alif Haidhar Halim and Nur Muhammad Danish Raisham - Abdullah, Muhammad Arif Musa; Halim, Muhammad Alif Haidhar; Raisham, Nur Muhammad Danish (2023)
Cryptography is a study or practice of secure communication that allow only the sender and the intended recipient which can help to avoid security issues. Cryptography converts the original message, which is called plaintext, into gibberish which is known as ciphertext through certain methods. The message is then sent to the recipient in this form, then the recipient can convert the ciphertext into plaintext using the same or different key to convert it back to plaintext and get the original message. RSA Cryptography is able to verify the receiver of the message but the sender can be a third-party member. RSA Digital Signature is able to verify the sender but the receiver can be a third-party member. Shamir’s Three Pass Protocol is able to make exchanging messages cannot be broken by third-party members however there is no way to verify the sender or receiver of the message. The objective of the study is to develop a modified multi-prime RSA digital signature cryptosystem and implement the multi-prime RSA digital signature cryptosystem into Shamir’s Three Pass Protocol. The methodology is sending the messages using Shamir’s Three Pass Protocol but the encrypted message will be signed using RSA digital signature method to be able to verify the sender and receiver. The study is hopefully able to help in boosting the security level in cybersecurity sectors.